Redox-responsive chemosensitive polyspermine delivers ursolic acid targeting to human breast tumor cells: The depletion of intracellular GSH contents arouses chemosensitizing effects - Ji, X.; Tang, Q.; Pang, P.; Wu, Jian-Ping; Kirk, Brett; Xu, J.; Ma, D.; Xue, W. (Elsevier BV, 2018)
Antitumor efficacy of ursolic acid (UA) is seriously limited due to its low hydrophilicity and needy bioavailability. To overcome these obstacles, chemosensitive polyspermine (CPSP) conjugated with UA and folic acid (FA) as a novel targeted prodrug was designed and successfully synthesized in this investigation. This prodrug not only showed high aqueous solubility, GSH-triggered degradation and good biocompatibility, but also exhibited better inhibition effect on the tumor cells proliferation in comparison with free UA. FA-CPSP-UA could down-regulate the generation of GSH and manifest excellent ability in enhancing antitumor efficacy. In addition, FA-CPSP-UA could inhibit the expression of MMP-9, which led to restricting MCF-7 cells migration. Taken together, the results indicated that FA-CPSP-UA, as a carrier, can efficiently deliver UA to folate receptor positive cancer cells and improve tumor therapy of UA by Chemosensitive effect.